PENGGUNAAN SUMBER BELAJAR PADA PEMBELAJARAN TEMATIK KELAS IV DI SDN WONOKERSO II KABUPATEN MALANG - Riska Dwi Pratiwi; Mohammad Afifulloh; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is based on research on the use of learning resources in thematic learning activities in class IV SDN Wonokerso II which is based on procurement, use, and constraints related to learning resources. In Wonokerso II Elementary School, the procurement of learning resources is still focused on purchases and donations, which causes a lack of variety of learning resources. The use of learning resources in class IV is also not optimal because the facilities for supporting the use of learning resources are not yet complete so that the teacher experiences obstacles in the learning activities carried out. The purpose of this research is to find out the problem and provide the best solution for students, teachers and schools to be even better. This type of research is a qualitative descriptive approach to data collection using observation / observation, documentation, and interviews. Data analysis uses data reduction, data presentation, data analysis and drawing conclusions. The results of this study are the use of learning resources in class IV SDN Wonokerso II is quite good and meets the current educational standards. However, it still has shortcomings that are expected to be corrected by teachers and schools.Keywords: Learning resources, class IV, SDN Wonokerso II